A novel high step-up DC–DC converter based on three-winding coupled inductor. Issue 1 (2nd January 2019) - Mahmoudi, Mohsen; Ajami, Ali; Babaei, Ebrahim
Abstract: In this paper, a novel boost DC/DC converter is proposed. The existence of the three-winding coupled inductor in the proposed topology causes an increase in voltage gain. Another advantage of suggested topology is that by reducing the turn's ratio of the coupled inductor the voltage gain of converter is increased. In the proposed converter the stored energy in the leakage inductance is recovered by utilizing a passive clamp circuit. Moreover, in the proposed topology, voltage stress on the main switch is decreased. As a result, a power switch with lower resistance RDS (ON) and the lower number of windings turn are caused to reduction of power losses. Operation rules and steady-state analysis of the proposed converter are explained completely. In order to evaluate the effectiveness of the proposed converter, a 200 W laboratory prototype is implemented. Experimental results approve the theoretical analysis of the proposed high step-up converter.